STUDENTS’ PERCEPTIONS TOWARDS ORAL CORRECTIVE FEEDBACK IN A SPEAKING CLASS - Sri Mulyani; Nurfajri Ningsih; Nurul Insiqamah Setyaningrum (Universitas Islam Negeri Alauddin Makassar, 2022)
This research aimed to find out students’ perceptions towards oral corrective feedback in a speaking class and the types of oral corrective feedback used by the lecturer. This study applied qualitative research design. Thirteen students had contributed to this research as the respondents. The data were collected by using open ended questionnaire and interview. The collected data were analyzed by applying thematic analysis. This study found students’ perceptions that covered three main themes, namely (1) the benefits of oral corrective feedback include increasing students’ knowledge, being a helpful way to improve students’ speaking ability, and giving positive impacts on students’ learning; (2) the drawbacks of oral corrective feedback include causing nervousness, causing unappreciated feeling, and causing embarrassed and traumatic feeling; and (3) students’ expectations of oral corrective feedback include motivating, encouraging and constructive oral corrective feedback, and appropriate timing in giving oral corrective feedback. In addition, this research also showed that the types of corrective feedback used by the lecturer in the speaking class were recast, elicitation, and explicit correction.